Al-Bīrūnī’s India, Chapter 14: An Account of Indian Astronomical, Mathematical and Other Literature - Verdon, Noémie; Yano, Michio (History of Science in South Asia, 2020)
This article provides a new English translation of Chapter 14 of al-Bīrūnī's Kitāb taḥqīq mā li-l-Hind. The whole book was translated by E. Sachau (as Alberuni's India) more than 100 years ago. Thanks to the more recent work by David Pingree, especially the Census of the Exact Sciences in Sanskrit, we can offer many improvements and additions to Sachau's translation. We focused our attention to Chapter 14 of the same book where we find much interesting information about the history of Indian astronomy and mathematics. In the Appendix we have compared the table of contents of the Brāhmasphutasiddhānta as reported by al-Bīrūnī (in Arabic) and those given in Dvivedin's Sanskrit text.